Unsicherheiten der EU-Osterweiterung - Gowan, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
Main problems of eastwards enlargement of the EU are caused by the EU itself. Before the East European states applying for membership can be integrated, the EU has to reform its expenditure, especially the structural Fund. Also the Common Agrarian Policy needs a fundamental reform. But these reforms are delayed and the applicants are burdened with new tests and requirements. Some groups demanding a swift enlargement try to use the new East European members for social dumping in Western Europe.